2017
DOI: 10.1002/tee.22568
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of massive antenna systems employing parallelogram planar arrays

Abstract: This paper experimentally verifies how the parallelogram planar array (PPA) can improve the space division multiplexing (SDM) performance of multiuser massive multiple-input multiple-output (MIMO) in line-of-sight (LOS) channels. PPA can reduce the spatial channel correlation (inter-user correlation) without any increase in processing load. Channel state information (CSI) of up to 94 antenna elements is measured with simplified test equipment in an outdoor propagation environment. Assessment of the measured CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The effects of antenna element types with uniform array geometries on the correlation and the capacity have been investigated in [10][11][12][13][14]. The uniform horizontal linear, the uniform vertical linear and the uniform planar antenna arrays consisting of 64 elements with half-wavelength separation are compared in [14], and it was shown that the horizontal linear array performs better than others in terms of channel separability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of antenna element types with uniform array geometries on the correlation and the capacity have been investigated in [10][11][12][13][14]. The uniform horizontal linear, the uniform vertical linear and the uniform planar antenna arrays consisting of 64 elements with half-wavelength separation are compared in [14], and it was shown that the horizontal linear array performs better than others in terms of channel separability.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of array geometry, a parallelogram antenna array (PPA) was proposed to reduce the channel correlation in [12]. The performance of the PPA was evaluated using system-level simulations and experiments in [13] where it was concluded that the PPA mitigates the overall channel correlation compared to uniform arrays. However, this study did not consider the spaces occupied by the antenna arrays, hence, the PPA geometry causes a wider antenna array size because of its parallelogram shape.…”
Section: Introductionmentioning
confidence: 99%
“…RSs are uniformly distributed within the range of 45 • ≤ ϕ ≤ 135 • (horizontal) and 90 • ≤ θ ≤ 95 • (looking down). Thanks to the low spatial correlation nature provided by the PPA, the simplified threshold based RS scheduling is applied[31,32]. Combination of RSs is determined such that their spatial correlation is lower than the threshold of 0.3.…”
mentioning
confidence: 99%